2011
DOI: 10.1111/j.1398-9995.2011.02598.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen proteases compromise the airway epithelial barrier through degradation of transmembrane adhesion proteins and lung bioactive peptides

Abstract: Pollen grains with distinct allergenic abilities release proteases that might be involved in the sensitization to a range of airborne allergens by facilitating allergen delivery across the epithelium and also contribute directly to the inflammation characteristic of allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 33 publications
7
99
1
2
Order By: Relevance
“…Finally, PAR stimulation opens tight junctions (TJ) by the secretion of metalloproteinase 9 [56]. Furthermore, it was described that some pollen grains release proteases with serine and/or amino peptidase activity which cleave transmembrane adhesion proteins facilitating para-cellular allergen delivery across Calu-3 human EC line and likely contributing to allergic sensitization [57]. Interestingly, in a recent study the protease activity of allergens was directly linked to TLR4 activation.…”
Section: Effect Of Proteases On the Epithelial Barriermentioning
confidence: 99%
“…Finally, PAR stimulation opens tight junctions (TJ) by the secretion of metalloproteinase 9 [56]. Furthermore, it was described that some pollen grains release proteases with serine and/or amino peptidase activity which cleave transmembrane adhesion proteins facilitating para-cellular allergen delivery across Calu-3 human EC line and likely contributing to allergic sensitization [57]. Interestingly, in a recent study the protease activity of allergens was directly linked to TLR4 activation.…”
Section: Effect Of Proteases On the Epithelial Barriermentioning
confidence: 99%
“…While 16HBE 14o-cells have been reported to exhibit morphological features including apical microvilli and cilia (Cozens et al, 1994), in our experience cilia are absent from polarized 16HBE 14o-cultures. In addition to their use for toxicology (Forti et al, 2010(Forti et al, , 2011 and drug transport studies, 16HBE 14o-and Calu-3 cell lines are frequently used for analysis of pathways involved in barrier function in response to environmental agents including allergens (Vinhas et al, 2011;Wan et al, 2001), particulates (Banga et al, 2012), cigarette smoke (Heijink et al, 2012) or viral infections (Harcourt et al, 2011;Rezaee et al, 2011). The other frequently used bronchial epithelial cell line, BEAS2B (Reddel et al, 1988), is not of value for transport studies as it fails to form an appreciable barrier (Forbes and Ehrhardt, 2005).…”
Section: Cfdeo-/6rep-cftrmentioning
confidence: 99%
“…It has previously been reported that proteases and lipid components of pollen extracts have the potential to interfere with the barrier functions of bronchial epithelial cells [14,15,20]. For example, pollen from Giant Ragweed, White Birch, Kentucky Blue Grass or Easter Lily have been shown to disrupt epithelial tight junctions with loss of occludin, ZO-1 and claudin-1 from the junctions [15].…”
Section: Figurementioning
confidence: 99%
“…Besides their modulatory effect on immune cells [13], components of pollen also have the potential to affect the epithelial barrier. Using epithelial cell lines, such as Calu-3, it has been suggested that proteases released by pollen interfere with epithelial barrier functions [14,15]. However, these cell line-based models do not recapitulate the in vivo epithelium: they are undifferentiated, lacking cilia, goblet cells and mucus secretions that protect the cell surface from components of the inhaled environment [16].…”
Section: Introductionmentioning
confidence: 99%